The Scot who loved me - Conkle, Gina (Conkle, Gina. Scottish treasure, 2021)
"The first in a daring new Scottish historical series about a woman determined to return Scottish treasures to the Highlands and the only man who can help her--the lover she once abandoned."--Page 4 of cover.